The Effect Of Gembili Flour Substitution (Dioscorea Esculenta L.) In Making Chicken Filled Dumpling Skins Regarding Physical Properties And Sensory Quality - Putri, Regita Ardita; Sachriani, Sachriani; Ridawati, Ridawati (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of gembili flour substitution in the production of chicken-filled wonton wrappers on the physical properties andSensory quality tests. The research was conducted at the Food Processing Laboratory, Department of Culinary Education, Universitas Negeri Jakarta. The study period was from May 2024 to September 2025. The research method used was an experimental method. The samples in this study were chicken-filled wonton wrappers substituted with gembili flour at levels of 5%, 10%, and 15%. Based on the results of statistical hypothesis testing using ANOVA for the physical properties test, it was found that the substitution of gembili flour had no significant effect on cooking loss. Furthermore, the results of statistical hypothesis testing using the Kruskal-Wallis test showed that there was no significant effect of gembili flour substitution on all sensory quality aspects evaluated, including the aroma of the gembili flour in the wrapper, the aroma of the chicken filling, the color of the wrapper, the taste of the wrapper, the taste of the filling, the taste of the gembili flour in the wrapper, texture (crispiness), and oil absorption. The conclusion of this study recommends the 15% gembili flour substitution in chicken-filled wonton wrappers to be further developed as a product with commercial potential and as an effort to promote the utilization of gembili flour as a local food ingredient.